Vigilantism in Ghana: Trends, Victim Characteristics, and Reported Reasons - Annor, F.; Adzimah‐Alade, M.; Akotia, C.S.; Quarshie, E.N-B. (The Howard Journal of Crime and Justice, 2020)
Vigilantism is gaining popularity in Africa as a means of self-defence, enacting justice, policing morality, and sanctioning (perceived) wrongdoings. Drawing on content analysis of 172 media reports from 2001 to 2018, this study examined the trends and patterns of vigilantism, characteristics of victims, and reported reasons for recourse to vigilantism within the Ghanaian context. Results showed a considerable increase in reported cases of vigilantism within the 18-year period, with most of the cases reported in urban settings. Theft and robbery emerged as the most frequently suspected crimes for which victims were attacked and, in many cases, killed. The study underscores the implications of vigilantism in terms of disdaining human life and dignity. It calls for the need to revisit the justice administration systems and punishment procedures, as well as resourcing and empowering law enforcers to fight crime, including vigilantism
Research Article
Keywords: Ghana; law enforcement; mob justice; vigilantism; violence